2019
DOI: 10.1177/0890334419830991
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Lactogenesis II is Associated With Lower Sleep Efficiency and Greater Variation in Nightly Sleep Duration in the Third Trimester

Abstract: Background. Metabolic and hormonal disturbances are associated with sleep disturbances and delayed onset of lactogenesis II. Research Aims. The aim of this study was to measure sleep using wrist actigraphy during gestation weeks 22 and 32 to determine if sleep characteristics were associated with blood glucose, body mass index, gestational related disease, delayed onset of lactogenesis II, or work schedule. Methods. Demographic data were collected at study intake from primiparous women who wore a wrist actigra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 47 publications
1
12
1
Order By: Relevance
“…Previous studies reported overall activity levels of pregnant women were decreased and onset of activity shifted to an earlier time relative to non-pregnant states [31]. We found no difference in time of waking or start of sleep time between gestational weeks 22 and 32 in this population of women [18], but there was a shift in time of peak of activity to nearly an hour earlier in the third trimester relative to second trimester. Mean activity (mesor) of women in our population also decreased as pregnancy progressed from gestational weeks 22 to 32.…”
Section: Circadian Rhythms Become Attenuated As Pregnancy Progresses contrasting
confidence: 60%
See 4 more Smart Citations
“…Previous studies reported overall activity levels of pregnant women were decreased and onset of activity shifted to an earlier time relative to non-pregnant states [31]. We found no difference in time of waking or start of sleep time between gestational weeks 22 and 32 in this population of women [18], but there was a shift in time of peak of activity to nearly an hour earlier in the third trimester relative to second trimester. Mean activity (mesor) of women in our population also decreased as pregnancy progressed from gestational weeks 22 to 32.…”
Section: Circadian Rhythms Become Attenuated As Pregnancy Progresses contrasting
confidence: 60%
“…The remaining were withdrawn by research staff due to lack of compliance to study protocol. There was no difference in demographic variables between recruited, retained and withdrawn populations [18,19].…”
Section: Population and Settingmentioning
confidence: 77%
See 3 more Smart Citations